Nursing practice environment in intensive care unit and professional burnout - Gisele Möller; João Lucas Campos de Oliveira; Daiane Dal Pai; Karina Azzolin; Ana Maria Müller de Magalhães (SciELO, 2021)
ABSTRACT Objective: To evaluate and compare the nursing practice environments in Intensive Care Units of a public and private hospital and the prevalence of burnout among nursing professionals. Method: Cross-sectional, descriptive study with a quantitative approach to the data. The data collection took place between October 2018 and March 2019, and it was carried out through a questionnaire with socio-occupational variables and with metrics of intensity. The practice environment was assessed through the Nursing Work Index Revised (NWI-R); and the burnout was assessed by the Maslach Burnout Inventory (IBM). We included professionals with, at least, six months of employment, and those who were on leave or on a fixed-term employment contract were excluded. Results: The sample consisted of 296 professionals. We found Favorable environments in both institutions, however, low results in the subscales autonomy, control and organizational support in the private hospital. The prevalence of burnout among nurses was 2.5% in the public hospital and 9.1% in the private hospital, and among nursing technicians, it was 9.5% and 8.5%, respectively. Conclusion: The control of the environment, autonomy and support were considered critical points, referring to the importance of assessing institutions factors, that can improve the working conditions for the nursing team.